Internationalization of the sharing economy in emerging markets. (c2019) - Masri, Karam Salah El (2018)
The Sharing Economy has been a constantly growing field for the last several years and its expansion has reached numerous countries around the world, as notable from the records of its leading companies, AirBnB and Uber. Moreover, the collaboration of traditional companies with Sharing Economy ones (such as BMW and Just Park) demonstrates the impact and relevance that the Sharing Economy has accomplished and the grounded presence it will most likely maintain. However, due to the unique nature of the Sharing Economy, its internationalization success and acceptance in emerging markets may vary due to several variables, many of which are related to culture, economic level, and other deciding factors. Furthermore, the literature under this topic is lacking and calls for more research. Thus, given the promising compatibility of the Lebanese market with the sharing economy model and the benefits it provides, this exploratory research was undergone to shed some light on the internationalization of the Sharing Economy in Lebanon and the willingness of the Lebanese youth to be part of it, while studying several other factors that could possibly affect this willingness. The research was done by exploring the Liability of Newness of the car-hailing apps Uber and Careem, and its relationship with the willingness of the Lebanese youth to use such apps. Furthermore, the relationship between this willingness and the four constructs of Online Trust, Consumer Innovativeness, Online Social Platform Habits, and Price Willingness was explored. Results show that there is a strong relationship between price willingness and willingness to use the service, a considerable relationship between Liability of Newness and willingness to use the service, a slight relationship between Online Sharing Habits and willingness to use the service, and weak relationships between each of Online Trust and Consumer Innovativeness with willingness to use the service. The results of the individual constructs Liability of Newness and willingness to use the service bode well for the future of the car-hailing apps in Lebanon.